Noun classification in Wolof when affixes are not renewed - Fiona McLaughlin (Studies in African Linguistics)
The Wolof noun class system exhibits a variety of class assignment strategies based on the intersection of semantic, morphological, phonological and sociolinguistic criteria. This study examines and analyzes the many strategies for class assignment that have coalesced in the Wolof noun class system, including the tendency towards a single default class, and an unusual copy process in which phonological material is copied from the stem to the class marker in a process that looks superficially like reduplication. Wolof noun classification is examined within the comparative context of its two closest sister languages, Pulaar and Seereer-Siin, and is shown to contrast with them in that the disappearance of class prefixes did not entail their replacement by suffixes. Finally, an argument is made that noun class systems like that of Wolof which appear to be somewhat incoherent from a semantic point of view are actually typical because noun classification is not only an artifact of the human mind, but also an artifact of human language.